2005
DOI: 10.1177/089875640502200402
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Identification of Lymphatic Vessels in the Periodontium of Equine Cheek Teeth

Abstract: Immunohistochemical detection of lymphatic capillaries was performed in the periodontium of maxillary and mandibular cheek teeth from 6 horses (aged 3-23 years). Tissue sections of the periodontium were taken at 4 different horizontal levels along the long axis of the tooth. The specimens were processed for immunoreaction with anti-Prox1, in order to distinguish lymphatic endothelium from blood vascular endothelium. Lymphatic vessels were detected in all periodontal tissues except for the dental cementum. Lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…To the authors’ knowledge, this is the first reported case in which PROX‐1 was used to aid in the diagnosis of a lymphangiosarcoma in a horse. PROX‐1 expression has also previously been reported in one case of feline lymphangiosarcoma . The neoplasm origin in the present case was confirmed by the positive detection of this antigen, and the authors suggest that PROX‐1 staining should be considered when there is need for further differentiation of an angiosarcoma in a horse.…”
Section: Discussionsupporting
confidence: 84%
“…To the authors’ knowledge, this is the first reported case in which PROX‐1 was used to aid in the diagnosis of a lymphangiosarcoma in a horse. PROX‐1 expression has also previously been reported in one case of feline lymphangiosarcoma . The neoplasm origin in the present case was confirmed by the positive detection of this antigen, and the authors suggest that PROX‐1 staining should be considered when there is need for further differentiation of an angiosarcoma in a horse.…”
Section: Discussionsupporting
confidence: 84%
“…Lyve1-positive vessels have been detected in the lamina propria in gingiva and in the free oral mucosa in mice (835, 1096). Prox1 expression has also been identified in equine gingival lymphatics (1021). Inflammation of the gingiva leads to formation of crevicular fluid and accumulation of CD45+ cells.…”
Section: Organization and Anatomy Of The Lymphatic Systemmentioning
confidence: 99%
“…Whether there is lymphatic drainage from the periodontal ligament is uncertain since conflicting data have been published. Lymphatic vessels have not been detected in the rat apical periodontal ligament [37] or in human apical lesions [38], in contrast to findings in horse periodontal ligament lymphatic vessels where lymphatic vessels have been shown [39]. If fluid from the periodontal ligament is drained from lymphatic vessels within the tissue or if fluid is transported through the interstitium into adjacent tissue, supplied with lymphatic vessels, remains to be investigated.…”
Section: Normal Distribution and Function Of Lymphatic Vessels In Ginmentioning
confidence: 91%
“…3), whereas VEGF-D is only found in some few immune cells in the connective tissue [42]. The lymphatic marker Prox1 has been shown in gingival lymphatic vessels [39] and activity in the homeobox gene Prox1 is necessary and sufficient to maintain a lymphatic endothelial fate [43]. Lymphatic endothelial cells are one of the few differentiated cell types that require a constant expression of a particular 'instructor' gene (in this case Prox1) to maintain their phenotype [44].…”
Section: Normal Distribution and Function Of Lymphatic Vessels In Ginmentioning
confidence: 98%